Sovereignty, Religion and Law in the British Empire: Raja Rammohan Roy's Public Hermeneutics in His Times. (August 2019) - Govind, Rahul
Raja Rammohan Roy has been called various things, from the first Indian liberal and a 'maker of modern India' to one who could bring about little more than a caricature of promised transformation. That Roy saw himself as a subject of the English King is much less analysed. The following essay takes this self-perception of Roy as a 'British subject' as a clue to develop a twofold problematic on the nature of religion and law in Roy's lifetime, that is, between the late eighteenth and early nineteenth century. (a) We emphasize the importance of the King of England, and the importance of Kingship in which religion and law cannot be disentangled. This is established through an examination of the institutional arrangements in relationship to Kingship in the British Isles and the subcontinent, a study of S. T. Coleridge's On the Constitution of the Church and State (London: Hurst, Chance and Co., 1830) and John Austin's Province of Jurisprudence Determined (Delhi: Universal Publishers, 2012), amongst lesser known texts. (b) From an investigation into this religio-political constitution, we will explore the other dimensions opened up in Roy's self-perception as a subject, that is, the relationship between religion, law and public reason in colonial India. By Roy's 'public hermeneutics', we mean his arguing in the public medium of print as much as for a public (the colonial state and the reading public). But we also mean his use of reason in a sustained fashion so as to critique social and legal conditions. His arguments in structural and substantive terms, as we show, allow one to re-think the relationship between religion, law and universality.